2003
DOI: 10.1021/jp0220276
|View full text |Cite
|
Sign up to set email alerts
|

Control of Reactivity in C−H Bond Breaking Reactions on Oxide Catalysts:  Methanol Oxidation on Supported Molybdenum Oxide

Abstract: Oxidation of organic substrates on metal oxide catalysts can be viewed as entailing a transfer of electrons from the organic moeity to the catalytic center, and is expected to involve the electron-accepting levels in the metal center. This investigation deals with the study of the electron-transfer processes associated with the C-H bond breaking reaction in adsorbed methoxide species in the course of methanol oxidation on supported MoO 3 . It is shown that the activity of a series of catalysts duly correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…38 A similar argument seems plausible for methanol oxidation, which occurs via rate-determining C-H bond activation steps, normally associated with the formal reduction of metal centers. Support effects were substantiated when Oyama et al 39 showed that the activity of a catalyst correlates with the density of unoccupied electronic states; MoO x deposited on support materials that readily accept electron density from reducing C-H bond cleavage steps in methanol oxidation result in higher conversion rates. 39 This reasoning becomes less unequivocal for the observed correlations between reducibility and DME oxidation rates, because H-abstraction appears to be kinetically irrelevant and C-O bond cleavage, which limits reaction rates, does not require the formal reduction of Mo 6+ centers.…”
Section: Isotopic Evidence For the Involvement Of Lattice Oxygen Atommentioning
confidence: 99%
See 1 more Smart Citation
“…38 A similar argument seems plausible for methanol oxidation, which occurs via rate-determining C-H bond activation steps, normally associated with the formal reduction of metal centers. Support effects were substantiated when Oyama et al 39 showed that the activity of a catalyst correlates with the density of unoccupied electronic states; MoO x deposited on support materials that readily accept electron density from reducing C-H bond cleavage steps in methanol oxidation result in higher conversion rates. 39 This reasoning becomes less unequivocal for the observed correlations between reducibility and DME oxidation rates, because H-abstraction appears to be kinetically irrelevant and C-O bond cleavage, which limits reaction rates, does not require the formal reduction of Mo 6+ centers.…”
Section: Isotopic Evidence For the Involvement Of Lattice Oxygen Atommentioning
confidence: 99%
“…Support effects were substantiated when Oyama et al 39 showed that the activity of a catalyst correlates with the density of unoccupied electronic states; MoO x deposited on support materials that readily accept electron density from reducing C-H bond cleavage steps in methanol oxidation result in higher conversion rates. 39 This reasoning becomes less unequivocal for the observed correlations between reducibility and DME oxidation rates, because H-abstraction appears to be kinetically irrelevant and C-O bond cleavage, which limits reaction rates, does not require the formal reduction of Mo 6+ centers. It appears, however, that electron density at cation sites increases gradually along the reaction sequence, instead of occurring sharply during the formal reduction assumed to occur at the H-abstraction step.…”
Section: Isotopic Evidence For the Involvement Of Lattice Oxygen Atommentioning
confidence: 99%
“…One of these similarities is the support effect, which is assumed to be related to the supporting metal oxide and strongly influences the reaction turn-over frequency (TOF). For methanol oxidation it is found that the TOF increases when changing the support from: [2][3][4][5] MoO x /SiO 2 < MoO x /Al2O 3 ! MoO x /TiO 2 < MoO x /ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[12] These observations together with various kinetic studies, principally conducted through the combined efforts of research groups at Virginia Tech and Tokyo Institute of Technology, led to the proposal of a schematic reaction mechanism [Eqs. (1) and (2)]: [2,3,13] CH 3 OHþMoþO ! MoÀOCH 3 þOÀH ð1Þ…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation